The 2015 and 2016 U.S. Homicide Rate Increases in Context. Issue 3 (August 2019) - McDowall, David
The U.S. homicide rate increases of 2015-2016 occurred within a longer recorded history of trend variations. This article examines the place of the 2 years within this history and considers if they were unusual. An analysis of more than five decades of panel data finds that 2015 and 2016 were, in fact, somewhat unusual, but not far outside the normal range of variation. The analysis also provides no evidence that changes like those in 2015-2016 can predict future trends. As a more general matter, this article argues for increased attention to the typical characteristics of crime rate changes.